2020
DOI: 10.1111/vcp.12926
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of normal reference intervals in dogs using a viscoelastic point‐of‐care coagulation monitor and its comparison with thromboelastography

Abstract: BackgroundViscoelastic coagulation devices are a useful adjunct to the evaluation of hemostasis in veterinary patients. VCM Vet is a point‐of‐care device that is simple in operation and could be used to diagnose and trend hemostatic abnormalities in sick patients. VCM Vet does not use activators.ObjectivesWe aimed to establish reference intervals (RIs) for VCM Vet in a healthy adult canine population and concurrently perform thromboelastographic (TEG) analysis on these samples with and without tissue factor (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(78 citation statements)
references
References 24 publications
5
71
2
Order By: Relevance
“…At standard assay temperature of 37°C and using institutionally derived RIs, 2 12 patients had prolonged R time with none having shortened R; 6 had an increased K time with none having shortened K; 7 had a decreased alpha angle and none had an increased alpha angle; 2 had a low MA with 20 having increased MA. Comparisons between analyses at the 2 temperatures showed very high correlation for R and MA values, high correlation for alpha and K values, and moderate correlation for LY30 and LY60, with significance documented for all variables (Table 2; Figs.…”
Section: Resultsmentioning
confidence: 99%
“…At standard assay temperature of 37°C and using institutionally derived RIs, 2 12 patients had prolonged R time with none having shortened R; 6 had an increased K time with none having shortened K; 7 had a decreased alpha angle and none had an increased alpha angle; 2 had a low MA with 20 having increased MA. Comparisons between analyses at the 2 temperatures showed very high correlation for R and MA values, high correlation for alpha and K values, and moderate correlation for LY30 and LY60, with significance documented for all variables (Table 2; Figs.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that viscoelastic tests run on NWB and without activators are subject to more variabilities than their treated and activated counterparts. Such variabilities may include contact activation, operator-dependent factors, and other preanalytical factors ( 6 , 10 ). These variabilities may explain the differences in CT and MCF between NWB and CWB samples.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the present study's low within-sample variation is its use of only four analyzers, whereas the manufacturer used eight analyzers to generate their data. Previous studies involving humans and equids have shown that variability may exist between different operators conducting viscoelastic tests, thus reducing the number of operators may help to reduce within sample variation ( 5 , 6 , 17 ). Inter-operator variability has been studied using both TEG and rotational thromboelastometry, though inter-operator variability is currently not known for the VCM Vet device; however, a proposed advantage of the utilized cartridge-based viscoelastic testing system is that the cartridge system could reduce inter-operator variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this study is the first to demonstrate use of VCM Vet TM to analyze blood coagulation properties in mice. To date, other investigators have published studies using VCM Vet TM to analyze blood from cats [7, 8], dogs [14], and bats [10]. In this study, we determined VCM Vet TM RIs for healthy mature adult C57BL/6N mice and reference value ranges needed for blood coagulation testing in experimental and preclinical studies with mice.…”
Section: Discussionmentioning
confidence: 99%